Management's knowledge filter: entrepreneurship theory and the historic conceptual evolution of opportunism in management studies. Issue 3 (19th October 2021) - Muldoon, Jeffrey; Bendickson, Joshua S.; Gur, Furkan A.; Murphy, Patrick J.
Abstract : Purpose: This study aims to argue that opportunism is central to management thought and illustrate its evolution into a central element of the entrepreneurship theory. The authors show that many criticisms of opportunism tend to conflate the concept with other theoretic traditions. Design/methodology/approach: The authors trace foundational works by Taylor, Mayo, Fayol, Barnard, Follett and Simon to limit opportunism under the guise of promoting cooperation in organizations. Findings: Opportunism is conceptualized in transaction cost economics as one of the most controversial concepts in management. While modern management is based on handling opportunism, it is bad for practice, as it ignores innovation, and damages trust and goodwill among organizational members. These interventions serve as a knowledge filter, damaging organizational entrepreneurship. Originality/value: By tracing the roots of opportunism in early management thought, the authors clarify ethical and entrepreneurial issues of mutual obligations in organizations. The authors also place workplace conflict to be a more coherent framework that better reflects the core concept of opportunism.